Analysis of the Local Area Network (LAN) at the Regional Office of the Ministry of Religion of Palembang City - Muhammad Rafliansyah Ibrahim Heriansyah; Karnadi (International Journal Cister, 2022)
At this time the development of Information and Communication Technology is very advanced in the community. While in developing countries, it only appears in urban areas and in industrial areas. This was also implemented by the Regional Office of the Ministry of Religion of the City of Palembang, as for problems that arose such as slow internet connections due to the uneven distribution of bandwidth. To overcome the existing problems the author suggests adding a proxy router that aims to block sites and manage bandwidth. The result is that all clients can get the same bandwidth and cannot open sites that are not allowed to be visited. A structured Local Area Network (LAN) is the best solution to solve the problems that exist in this agency, as well as with a structured Local Area Network (LAN) can achieve an effective and efficient job in supporting activities in this agency and can maintain confidential company data. The method used during this research the author uses the action research method.